Simultaneous size manipulation and red upconversion luminescence enhancement of CaF2:Yb3+/Ho3+ nanoparticles by doping with Ce3+ ions. Issue 23 (30th April 2019) - Yang, Xu; Yuan, Maohui; Wang, Rui; Zhao, Xiaofan; Yang, Zining; Han, Kai; Wang, Hongyan; Xu, Xiaojun
Abstract : Size manipulation and red upconversion luminescence enhancement are simultaneously realized in CaF2 :Yb 3+ /Ho 3+ nanoparticles by doping with Ce 3+ ions. Abstract : Harnessing the color tuning capability of upconversion nanoparticles (UCNPs) is of great significance in the field of advanced bioimaging and color display. Here, we report the tunable size and upconversion luminescence (UCL) multicolor in CaF2 :Yb 3+ /Ho 3+ /Ce 3+ UCNPs, which were synthesized by a facile hydrothermal method. It was found that the size of these UCNPs could be controlled (from 600 to 30 nm) by varying the concentration of Ce 3+ ions. Under the excitation of a 980 nm continuous-wave (CW) laser, the UCL color of these UCNPs can be tuned from green to red as the doped Ce 3+ ions gradually increase from 0 to 10 mol% and the red-to-green (R/G) ratio is enhanced remarkably. It is suggested that the cross-relaxation (CR) processes between Ho 3+ and Ce 3+ ions contribute to the tunable multicolor and enhancement of the R/G ratio. The mechanism of these processes is well supported by the time-resolved decay and near infrared (NIR) emission measurements.